Empowering central bank asset purchases: The role of financial policies - Matthieu Darracq Pariès; Jenny Körner; Niki Papadopoulou (European Central Bank (ECB), 2019)
This paper contributes to the debate on the macroeconomic effectiveness of expansionary non-standard monetary policy measures in a regulated banking environment. Based on an estimated DSGE model, we explore the interactions between central bank asset purchases and bank capital-based financial policies (regulatory, supervisory or macroprudential) through its influence on bank risk-shifting motives. We find that weakly-capitalised banks display excessive risk-taking which reinforces the credit easing channel of central bank asset purchases, at the cost of higher bank default probability and risks to financial stability. In such a case, adequate bank capital demand through higher minimum capital requirements curtails the excessive credit origination and restores a more efficient propagation of central bank asset purchases. As supervisors can formulate further capital demands, uncertainty about the supervisory oversight provokes precautionary motives for banks. They build-up extra capital buffer attenuating non-standard monetary policy. Finally, in a weakly-capitalised banking system, countercyclical macroprudential policy attenuates banks risk-taking and dampens the excessive persistence of the non-standard monetary policy impulse. On the contrary, in a well-capitalised banking system, macroprudential policy should look through the effects of central bank asset purchases on bank capital position, as the costs in terms of macroeconomic stabilisation seem to outweigh the marginal financial stability benefits.
Keywords: E44; E52; F40; 330; non-standard monetary policy; asset purchases; bank capital regulation; risk-taking; regulatory uncertainty; effective lower bound